Fifty Years of Contemporary Spanish Poetry (1939-1989) - José Olivio Jiménez (Studies in 20th & 21st Century Literature, 1992)
Fifty Years of Contemporary Spanish Poetry (1939-1989)
Keywords: contemporary Spanish poetry; Spanish poetry; poetry; poetry since the Civil War (1936-1939); overview; generational schematization; expository; exposition; methodology; generational methodology; critique; literary critique